2001 IEEE Porto Power Tech Proceedings (Cat. No.01EX502)
DOI: 10.1109/ptc.2001.964958
|View full text |Cite
|
Sign up to set email alerts
|

High-speed fault identification and protection for HVDC line using wavelet technique

Abstract: This paper describes a new high-speed HVDC line protection using wavelet technique, Based on the representation of the tavelling waves through wavelet modulus maxima, the protection criterions for HVDC line are proposed. Simulations are carried out for testing the criterions. And the influences of similar faults are discussed. The protection can detect the HVDC line fault well and identify the HVDC line fault clearly from the similar transients, such as commutation failure and AC single phase fault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…(s) (6 ) It is observed that the compensation matrix is independent of the voltages and current and is related to frequency dependent parameters. The proposed technique can be written in two steps:…”
Section: Principle Of Proposed Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…(s) (6 ) It is observed that the compensation matrix is independent of the voltages and current and is related to frequency dependent parameters. The proposed technique can be written in two steps:…”
Section: Principle Of Proposed Techniquementioning
confidence: 99%
“…So, it is very necessary to find the location of the fault accurately and employing protective measures for clearance of the fault. Various methods are employed for the protection of HVDC transmission lines [3]- [7]. Travelling wave protection is used as a primary protection and is unable to detect the line faults with high transition resistance.…”
Section: Introductionmentioning
confidence: 99%
“…where is the setting distance, is the propagation constant, and is the characteristic impedance, and are obtained by (4) where the line parameters are expressed in per-unit length and, in general, are frequency dependent; that is, , with in and in , and , with in and in . In practice, and can be assumed constant for the frequency range of power system studies.…”
Section: Proposed Protection Principlementioning
confidence: 99%
“…One is the reflectometry technique [4,5], which measures the time interval between the first arriving surge and its subsequent reflection at one side of the transmission line. Due to no information is required from the remote terminal, communication link is not necessary between them.…”
Section: Introductionmentioning
confidence: 99%